Overview of hirsutella-like anamorphs in Ophiocordyceps (Sordariomycetes, Ophiocordycipitaceae): introducing two new species and one new record from China - Shi-Wen Xie; De-Ping Wei; Jun-Zhi Qiu; Xing-Can Peng; Ji-Chuan Kang; Zhang-Jiang He; Zeng-Zhi Li; Chun-Ru Li; Shi-Ke Huang; Xian Zhang; Zhong-Liang Liu; Jing Bu; et al. (MycoKeys, 2025)
Ophiocordyceps, a species-rich genus in Ophiocordycipitaceae, is a holomorphic genus in which most of the species are reported with hirsutella-like anamorphs. In this study, we introduce two new species of hirsutella-like anamorphs from lepidopteran larvae (viz., Ophiocordyceps tielingensis sp. nov. and Ophiocordyceps keqinii sp. nov.). Ophiocordyceps radiata (syn. Hirsutella radiata), a new combination, exhibits a pathogenic association with a fly, and it is reported as a new geographic record from China, based on integrated morphological and molecular analyses. We provide a checklist of Ophiocordyceps species with hirsutella-like anamorphs and comprehensively review their characteristics of anamorphs and teleomorphs. These definitive findings establish a foundation for the classification and diversity of Ophiocordyceps species with hirsutella-like anamorphs.